Olive oil emulsion-based method for separation and identification of microplastics in matrices

Through the separation method based on olive oil emulsion, the problems of low efficiency and high cost of microplastic extraction in the prior art are solved, and efficient and low-cost microplastic separation and identification are achieved, which are suitable for complex substrates.

CN116558933BActive Publication Date: 2025-04-15OCEAN UNIV OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310228240.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-10
Publication Date
2025-04-15
Estimated Expiration
2043-03-10

AI Technical Summary

Technical Problem

The prior art is inefficient, cumbersome and costly when extracting microplastics from complex substrates, and traditional methods are difficult to apply to samples containing light organic matter.

Method used

Using the separation method based on the olive oil emulsion, an olive oil emulsion was prepared by preparing olive oil, emulsifier and water, and the sample solution was thoroughly mixed with the olive oil emulsion and added deemulsion, and the microplastics were enriched by demulsification treatment and left to stand.

Benefits of technology

It realizes efficient extraction of microplastics, with simple steps, low cost, green and environmentally friendly, suitable for microplastic separation in simple and complex substrates, and the identification of microplastic types through Raman spectroscopy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116558933B_ABST
    Figure CN116558933B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for separating and identifying microplastics in a matrix based on olive oil emulsion, and the method for separating microplastics in a matrix based on olive oil emulsion comprises the following steps: S1 prepares a sample solution; S2 prepares an olive oil emulsion with olive oil, an emulsifier and water as raw materials, wherein Tween 80 accounts for 3%-9% of the total volume of the raw material, glycerol accounts for 9%-36% of the total volume of the raw material, and the volume ratio of olive oil to water is 0.24-1; S3 fully mixes the sample solution with a certain volume of olive oil emulsion, wherein the olive oil emulsion is added to at least 60% of the total volume of the mixed solution; S4 adds a certain volume of demulsifier to the mixed solution, the volume of the demulsifier accounts for 40%-70% of the volume of the olive oil emulsion, and the demulsification treatment is performed for a period of time and then the mixture is allowed to stand for stratification, wherein the oil phase is an extraction solution enriched with a large amount of microplastics. The separation method has simple steps, low operating cost, wide application range, and a high extraction rate of microplastics separated by the method, and microplastics can be identified using Raman spectroscopy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of microplastics, and in particular to a method for separating and identifying microplastics in a matrix based on olive oil emulsion. Background Art

[0002] Plastic pollution is one of the major environmental pollution issues of concern worldwide. Plastic waste enters terrestrial and aquatic environments at a level of hundreds of millions of tons each year, and subsequent weathering causes large plastic fragments to degrade into small plastic fragments or even particles. According to the definition of the European Chemicals Agency, microplastics with a diameter of less than 5 mm have been found in different environmental matrices, such as soil, lakes, oceans and air. In addition, animal and plant foods and convenience products around the world are inevitably contaminated by microplastics because the environment of the raw materials is contaminated by microplastics. A greater challenge is that despite their small size, microplastics are persistent and harmful, posing potential risks to wildlife and humans. To this end, some extraction methods have been developed to eliminate microplastics from environmental and food samples. Traditional extraction methods include flotation, screening and filtration, which are either not very suitable for separating small microplastics or are associated with membrane fouling and wear problems. Microplastics further show resistance to chemical or microbial attacks due to their own hydrophobic characteristics. Therefore, it is necessary to design and develop advanced technologies to extract microplastics from various matrices.

[0003] At present, the enrichment of microplastics in samples is mainly based on the principle of filtration and density flotation, which uses the density difference between polymers and solid samples. Different saline solutions are added to the sample, and after oscillation and sedimentation, the supernatant is filtered with a vacuum pump, and the microplastics are collected on the filter. The most common separation solution consists of sodium chloride (NaCl), which has a density of 100,000, but other salts such as zinc chloride (ZnCl2), calcium chloride (CaCl2), sodium iodide (Nal), sodium polytungstate, and sodium bromide (NaBr) are also used to increase the density to extract higher density polymers. Nevertheless, this type of method is not suitable for samples containing light organic matter, such as cosmetics, soil, food, etc., with low separation efficiency and cumbersome and time-consuming separation process. For large-scale separation and filtration devices, the equipment is complex, the operating cost is high, and the complex matrix will clog the filter membrane.

[0004] Furthermore, people use the hydrophobicity of microplastics to enrich and separate microplastics. For example, magnetic particles can be used as magnetic medium carriers to separate microplastics under a magnetic field by utilizing hydrophobic effects. 2+ / Fe 3+The release of ions and related substances from these magnetic particles limits the application of this method. In addition, since oils are strongly hydrophobic solvents, they have been used to extract microplastics from complex samples and obtain high recoveries by virtue of hydrophobic interactions. However, high-yield extraction requires relatively large amounts of oil, so cost-effectiveness limits the industrial application of large amounts of oil for the extraction of microplastics.

[0005] To this end, we have developed a method based on olive oil emulsion to separate and identify microplastics in the matrix, which is not only low-cost and environmentally friendly, but also has a high microplastic removal rate and great application potential. Summary of the invention

[0006] In order to make up for the shortcomings of the prior art, the present invention provides a method for separating and identifying microplastics in a matrix based on olive oil emulsion, which has the advantages of high extraction rate, simple steps, low cost and wide application.

[0007] The technical solution adopted by the present invention to solve the above technical problems is:

[0008] A method for separating microplastics in a matrix based on olive oil emulsion, comprising the following steps:

[0009] S1: prepare the sample solution of microplastics to be separated;

[0010] S2: preparing an olive oil emulsion using olive oil, an emulsifier and water as raw materials in a high-speed disperser, wherein the emulsifier comprises Tween 80 and glycerol, Tween 80 accounts for 3%-9% of the total volume of the raw materials, glycerol accounts for 9%-36% of the total volume of the raw materials, and the volume ratio of olive oil to water is 0.24-1;

[0011] S3: the sample solution is thoroughly mixed with a certain volume of olive oil emulsion, wherein the olive oil emulsion is added to at least 60% of the total volume of the mixed solution;

[0012] S4: Add a certain volume of demulsifier to the mixed solution, the volume of the demulsifier accounts for 40%-70% of the volume of the olive oil emulsion. After a period of demulsification treatment, let it stand and separate into layers, where the oil phase is an extraction solution enriched with a large amount of microplastics.

[0013] In one example, the demulsifier in step S4 is DMSO, and the demulsification time is at least 13 hours.

[0014] In one example, the time in step S4 is at least 16 hours.

[0015] In one example, the amount of demulsifier added in step S4 is 50-70% of the volume of the olive oil emulsion.

[0016] In one example, the olive oil emulsion in step S3 is added to 70% of the total volume of the mixed solution.

[0017] In one example, in step S2, Tween 80 accounts for 5% of the total volume of the raw material, glycerol accounts for 27% of the total volume of the raw material, and the volume ratio of olive oil to water is 0.24-0.62.

[0018] In one example, the separated microplastic species include at least PS and PMMA.

[0019] In one example, the sample solution in step S1 includes a sample solution of a simple matrix and a sample solution of a complex matrix, wherein the sample solution of the complex matrix includes at least configured toothpaste water, soil water, sea water, and tea water.

[0020] In one example, the method for preparing toothpaste water is as follows: add toothpaste to water and stir thoroughly, let it stand and obtain the upper solution; the method for preparing soil water is as follows: first treat the soil with Fenton digestion solution, then mix the treated soil with deionized water, and obtain the upper solution; the method for preparing seawater is as follows: take seawater, let it stand for a period of time, and obtain the upper solution; the method for preparing tea water is as follows: brew tea leaves with boiling water, then let it stand for a period of time, and obtain the upper solution.

[0021] The present application also provides a method for identifying microplastics in a matrix based on olive oil emulsion, comprising the following steps: first preparing an extraction solution by a method for separating microplastics in a matrix based on olive oil emulsion, then collecting a Raman spectrum of the extraction solution, and determining the type of microplastics based on the characteristic peaks of the Raman spectrum.

[0022] The present invention adopts the above method, and has the advantages that:

[0023] 1. The microplastic separation method of the present application can not only remove microplastics with a high extraction rate, but also has simple steps, low use cost and is green and environmentally friendly, and has the advantage of industrial application in extracting microplastics.

[0024] 2. The microplastic separation method of the present application has a wide range of applications. In terms of sample types, it can be used not only for the separation and extraction of microplastics in simple matrices, but also for the separation and extraction of microplastics in complex matrices such as toothpaste, soil, tea, and seawater; in terms of microplastic size and concentration, it can be used for the separation of microplastics in a wider concentration range and size range.

[0025] 3. The microplastic separation method of the present application has an extraction rate that is equivalent to or higher than that of existing extraction methods. Under certain conditions, the extraction rate of PS microplastics can reach about 78%, and the extraction rate of PMMA microplastics can reach 87%.

[0026] 4. The type of the extracted solution separated by the microplastic separation method of the present application can be identified by Raman spectroscopy, which indicates that the identification method of the present application can be used for the identification of microplastics after emulsion separation. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a schematic diagram of the principle of separation and identification of microplastics of the present invention;

[0028] Figure 2 It is a characterization diagram of the effect of the content of each component on the particle size and PDI of olive oil emulsion;

[0029] Figure 3 This is a characterization diagram of the effects of pH, ionic strength and temperature on particle size and PDI of olive oil emulsion;

[0030] Figure 4 This is a characterization diagram of the effect of storage days on the particle size of olive oil emulsion;

[0031] Figure 5 This is a standard curve diagram of fluorescent PS and PMMA microplastics of different sizes;

[0032] Figure 6 Characterization diagram of the effect of demulsification time on the extraction rate of PMMA (a) and PS (b);

[0033] Figure 7 Characterization diagram of the effect of demulsifier type and addition amount on the extraction rate of PMMA (a) and PS (b);

[0034] Figure 8 Fluorescence microscopy images showing the effect of demulsifier types on the extraction of PMMA (a) and PS (b);

[0035] Fig. 9 Characterization diagram of the effects of DMSO addition amount and microplastic concentration on the extraction rate of PMMA (a) and PS (b);

[0036] Fig.10 This is a characterization diagram of how the concentration and size of PS microplastics affect their extraction rate;

[0037] Fig.11 A representation of the results involved in four comparative oil-phase emulsion microplastic separation experiments;

[0038] Fig.12 This is a characterization diagram of the effect of the amount of emulsion added on the extraction rate of PMMA and PS after microplastic separation experiments were carried out using tea water, sea water, soil water and toothpaste water as samples;

[0039] Fig.13 Raman spectra and Raman microscopy images of microplastic standards and microplastic identification experiments using deionized water as samples;

[0040] Fig.14 Raman spectra and Raman microscopic images of microplastic identification experiments using toothpaste water as samples. DETAILED DESCRIPTION

[0041] In order to clearly illustrate the technical features of the present solution, the present invention is described in detail below through specific implementation methods and in conjunction with the accompanying drawings. In the following description, many specific details are described to facilitate a full understanding of the present application. However, the present application can also be implemented in other ways different from those described herein. Therefore, the protection scope of the present application is not limited by the specific embodiments disclosed below.

[0042] The method of separating microplastics from a matrix based on olive oil emulsion in this application can not only be used to separate microplastics from simple matrices, but also overcome the defects of existing filtration methods, density flotation and other methods in separating complex matrix samples, and is expected to be applied to industrial separation of microplastics. In addition, the separation method of this application also has a high microplastic extraction rate. The high extraction rate indicates that this method has great potential for removing plastic pollutants and is also conducive to the identification of microplastics. See the schematic diagram of the separation and identification of microplastics. Figure 1 The separation principle is as follows: During the separation process, the dispersed phase of the olive oil emulsion will gradually gather around the microplastics, and through a coating process based on the principle of similar compatibility, a quasi-colloidal substance will be formed after demulsification to extract the oil phase, and then the microplastics will be extracted through hydrophobic action.

[0043] (I) Experimental study on olive oil emulsion

[0044] Preparation method: Olive oil emulsion was prepared using olive oil, Tween 80, glycerol and water as raw materials in a high-speed disperser (dispersion treatment at about 13000 rpm for about 7 minutes).

[0045] 1. Explore the effects of different composition variables on olive oil emulsion

[0046] In the specific preparation process, the olive oil emulsion prepared was characterized with the oil-water ratio as a variable, under the condition that the amount of Tween 80 added accounted for 5% of the total volume and the amount of glycerol added accounted for 27% of the total volume. The characterization results are shown in Figure 2 a; With the amount of Tween 80 added as a variable, the prepared olive oil emulsion was characterized under the conditions of an oil-water ratio of 0.42 and a glycerol addition amount of 27% of the total volume. The characterization results are shown in Figure 2 b; With the amount of glycerol added as a variable, the prepared olive oil emulsion was characterized under the conditions of an oil-water ratio of 0.42 and Tween 80 added in an amount of 5% of the total volume. The characterization results are shown in Figure 2 c.

[0047] pass Figure 2 a. Figure 2 b. Figure 2c It can be seen that when the volume ratio of olive oil to water is between 0.24-1, Tween 80 accounts for 3%-9% of the total volume of the raw material, and glycerol accounts for 9%-36% of the total volume of the raw material, the obtained olive oil emulsion has a smaller particle size and a lower PDI value, and the smaller particle size and polydispersity coefficient are conducive to the stability and uniform dispersion of the emulsion. Therefore, based on the above conditions, an olive oil emulsion with good stability and dispersibility can be constructed, which is conducive to the subsequent application in microplastic separation experiments to separate microplastics with a higher enrichment efficiency. For olive oil emulsions, Tween 80 as a surfactant can effectively reduce interfacial tension, which is conducive to the formation of smaller liquids, and the system tends to be more stable and evenly dispersed; glycerol, as an alcohol with an emulsifying effect, improves the stability of the emulsion by strengthening the combination of surfactants at the oil-water interface to form an oil-water interface film.

[0048] In addition, through Figure 2 It can be seen that when the oil-water ratio is 0.42, the olive oil emulsion has a better particle size and PDI value, which are 136.5nm and 0.254 respectively. Figure 2 b It can be seen that when the volume addition amount of Tween 80 is 5%, the olive oil emulsion has a better particle size value and PDI value, which are 136.2nm and 0.137 respectively. Figure 2 c It can be seen that when the volume addition amount of glycerol is 27%, the olive oil emulsion has better particle size and PDI value, which are 124.07nm and 0.151 respectively.

[0049] 2. Explore the effects of different external factors on olive oil emulsion

[0050] Under the conditions of oil-water ratio of 0.42, Tween 80 addition accounting for 5% of the total volume, and glycerol addition accounting for 27% of the total volume, the effects of emulsion pH value, ionic strength (NaCl), heat treatment (50°C temperature), and placement time on the particle size and PDI value of olive oil emulsion were investigated. The characterization results are shown in Figure 3 a. Figure 3 b. Figure 3 c and Figure 4 .

[0051] pass Figure 3 It can be seen from the figure that when the pH is 7.0, 9.0, and 11.0, the emulsion does not stratify (i), the particle size hardly changes (ii), and the PDI value is maintained at about 0.4 (ii). The emulsion has good dispersibility, indicating that the alkaline environment has no significant effect on the stability of the olive oil emulsion. When the pH is less than 7.0, due to the proximity to the isoelectric point of the emulsion droplets, the surface charge and electrostatic repulsion of the droplets are reduced, the emulsion stratifies, the particle size gradually increases, the PDI increases to 0.85, and the uniform dispersibility of the emulsion decreases. In summary, the droplet size of the olive oil emulsion does not change significantly within a larger pH range, especially in an alkaline environment, where it maintains good stability.

[0052] pass Figure 3 b It can be seen that with the increase of ionic strength, the olive oil emulsion showed slight stratification, but the average particle size of the emulsion remained basically unchanged, with a particle size value of about 151.05nm and a polydispersity coefficient below 0.25, indicating that under different ionic strengths, the emulsion still maintained a small particle size and polydispersity coefficient, maintaining a certain stability and uniform dispersion. This is mainly because the salt ions failed to change the interfacial film, and the Tween 80-stabilized emulsion had the ability to resist ion-induced droplet aggregation, and the emulsion was able to maintain stability and uniform dispersion. In summary, the olive oil emulsion has good stability and is expected to be used in the enrichment of microplastics in actual samples such as seawater.

[0053] pass Figure 3 c It can be seen that within 1h of heat treatment at 50℃, the olive oil emulsion did not show stratification, the particle size remained almost unchanged, and the PDI was about 0.25, indicating that a temperature change of 1h would not affect the particle size of the olive oil emulsion. When the heating time reached 1.5h, the olive oil emulsion did not show obvious flocculation, and the particle size increased to 153nm, but the PDI value was still about 0.25. When the heating continued to 2h, the olive oil emulsion stratified, and the particle size and polydispersity of the emulsion increased significantly, the particle size increased to 173nm, and the PDI was 0.412. Under continuous heating, the emulsion was destroyed, and the droplets aggregated into large droplets, resulting in an increase in particle size. The results show that within 1.5h, heating at 50℃ hardly affects the stability and dispersibility of the emulsion, and the olive oil emulsion has relatively good thermal stability.

[0054] pass Figure 4 It can be seen that under the same temperature condition (25°C), the same emulsion was stored for 0-9 days, and the particle size distribution of the olive oil emulsion was uniform and had only a single peak (129.4±4.76nm), which means that the particle size of the emulsion did not change substantially. This result shows that even after storage for 9 days, the olive oil emulsion still did not have obvious flocculation and stratification. It can be seen that the olive oil emulsion obtained in this application has good storage stability.

[0055] In summary, the olive oil emulsion obtained in the present application has good alkali stability, thermal stability and storage stability, and is less affected by salt ions, which indicates that the olive oil emulsion has good application prospects.

[0056] (II) Microplastic separation experiment

[0057] Polystyrene PS is a general-purpose plastic widely used in the manufacture of various consumer goods. As a hard solid plastic, it is usually used in food packaging, lightweight protective packaging, and dining tableware, and is closely related to food and human life. Polymethyl acrylate plastic PMMA is a representative plastic widely used in industrial production. For example, it can be used in optical glass, TV screens, acrylic boards, product advertising windows, architectural glass, and microfluidic chips. Both have been reported to be detected in organisms and are representative of hazards. Therefore, this application takes PS and PMMA microplastics as examples, conducts microplastic separation experiments on simulated samples containing microplastics, and calculates the extraction efficiency of the separated microplastics. The specific separation steps and calculation steps are as follows:

[0058] S1: prepare sample solution containing microplastic simulated sample;

[0059] S2: preparing an olive oil emulsion using olive oil, an emulsifier and water as raw materials in a high-speed disperser, wherein the emulsifier includes Tween 80 and glycerol, Tween 80 accounts for 3%-9% of the total volume of the raw materials, glycerol accounts for 9%-36% of the total volume of the raw materials, and the volume ratio of olive oil to water is 0.24-1;

[0060] S3: thoroughly mixing the sample solution with a certain volume of olive oil emulsion, wherein the olive oil emulsion is added to at least 60% of the total volume of the sample solution and the olive oil emulsion;

[0061] S4: Add a certain volume of DMSO to the mixed solution obtained in S3, and perform demulsification treatment by shaking with a vortex oscillator, and then let it stand to separate the layers. The oil phase is an extraction solution enriched with a large amount of microplastics, and the volume of the demulsifier accounts for 40%-70% of the volume of the olive oil emulsion.

[0062] S5: Take the upper and lower layer solutions and place them under a fluorescence spectrophotometer, select the excitation light wavelength corresponding to the plastic, and calculate the fluorescence intensity of the upper and lower layer solutions at the wavelength of the plastic emission light; among them, the excitation light wavelength of PS is 488nm, and the emission light wavelength is 515nm; the excitation light wavelength of PMMA is 488nm, and the emission light wavelength is 532nm;

[0063] S6: Prepare 0 mg / L, 100 mg / L, 200 mg / L, 300 mg / L, 400 mg / L, 500 mg / L, and 600 mg / L fluorescent plastic solutions, place them under a fluorescence spectrophotometer, select the excitation light wavelength corresponding to the plastic, calculate the fluorescence intensity of the solution at the emission light wavelength, and draw a standard curve of plastic concentration and fluorescence intensity;

[0064] S7: Subtract the fluorescence intensities of the upper and lower layers of the blank group (containing no microplastics) from the fluorescence intensities of the upper and lower layers of the experimental group, and substitute them into the standard curve to calculate the concentrations C1 and C2 of the upper and lower layers of fluorescent plastics separated by the method of the present application. Multiply the concentrations by the volumes V1 and V2 of the upper and lower layer solutions, respectively, to calculate the separation efficiency. Separation efficiency = (C1*V1) / (C1*V1+C2*V2).

[0065] According to step 6, the standard curves of 3μm, 100nm, 800nm ​​PS concentration and fluorescence intensity and the standard curve of 5μm PMMA concentration and fluorescence intensity were drawn respectively. Figure 5 .

[0066] 1. Using deionized water as the sample, microplastic separation experiments were carried out with microplastic size, microplastic concentration, demulsifier type, amount of demulsifier added relative to emulsion, and demulsification time as variables.

[0067] Use deionized water to prepare fluorescent microplastic sample solutions of different concentrations and sizes for later use. In the following experiments, the amount of sample solution is much smaller than the amount of emulsion added.

[0068] (1) A 3 μm PS and 5 μm PMMA microplastic separation experiment was conducted with demulsification time as a variable. The specific experimental conditions were as follows: in the sample solution, the plastic concentration was 100 mg / L; in the olive oil emulsion, the water-oil ratio was 0.42, the volume of Tween 80 was 5%, and the volume of glycerol was 27%; the demulsifier was DMSO, and the volume ratio was 50%; under the above experimental conditions, the fluorescence intensity of the microplastics was measured and the concentration and extraction efficiency were calculated at 3 h of demulsification treatment, and then the measurement and calculation were performed every 1 h. The characterization results of the PMMA microplastic extraction efficiency and demulsification time are shown in Figure 6 a, Characterization results of PS microplastic extraction efficiency and demulsification time are shown in Figure 6 b.

[0069] pass Figure 6 It can be seen from a that within 18 hours of demulsification treatment, the emulsion gradually formed two immiscible phases, PMMA microplastics were enriched in the upper layer, and the extraction rate increased monotonically with the enhancement of demulsification. Subsequently, the extraction rate tended to be constant at about 85%, forming an upper oil phase with olive oil as the main component and a lower water phase. Figure 6 As shown in Figure 2, as the demulsification time increases to 18 h, a distinct stratified oil-water phase is formed, and PS microplastics are enriched in the oil phase, with an extraction rate of about 78%. Among them, the extraction rate of PS microplastics is slightly lower than that of PMMA microplastics, because the hydrophobicity of PMMA is stronger than that of PS, which makes PMMA have a stronger hydrophobic interaction with oil droplets.

[0070] (2) The separation experiments of 3μm PS and 5μm PMMA microplastics were carried out with the type of demulsifier and the amount of demulsifier added as variables. The specific experimental conditions are as follows: the concentration of microplastics in the sample solution is 100 mg / L; the water-oil ratio in the olive oil emulsion is 0.42, the volume of Tween 80 is 5%, and the volume of glycerol is 27%; the volume ratio of the demulsifier is 50%, and the demulsification time is 18h; based on the above experimental conditions, microplastic separation experiments were carried out under three demulsifiers: DMSO (dimethyl sulfoxide), EtOH (ethanol), and ACN (acetonitrile), and each demulsifier was subjected to microplastic separation experiments under four volume conditions of 40%, 50%, 60%, and 70%. The characterization results of the extraction rate of microplastics, the type of demulsifier, and the amount of addition are shown in Figure 2. Figure 7 , Figure 7 The three lines in the figure correspond to DMSO, ACN, and EtOH from top to bottom. The extracts of microplastics after demulsification with DMSO (i), EtOH (ii), and ACN (iii) were characterized by fluorescence microscopy images at a demulsifier dosage of 50%. The characterization results are shown in Figure 8 (10 μm fluorescence microscopy image).

[0071] pass Figure 7 From a and 7b, we can see that the extraction rate of DMSO as a demulsifier for PMMA and PS microplastics is greater than that of ACN and EtOH. This is because at the oil-water interface, demulsifiers with branched structures occupy a larger surface area than linear demulsifiers, replacing more emulsifying molecules at the oil-water interface, and have the advantages of low dosage and high dehydration rate. At the same time, introducing some heteroatoms (such as N, O) into the molecular structure of the demulsifier to form hydrophilic groups will have a better demulsification effect. Specifically, Figure 7 In a, when the dosage of demulsifier increases, the extraction rate of PMMA microplastics in the emulsion system gradually increases. When the dosage of DMSO, ACN and EtOH as demulsifiers reaches 50% and the demulsification time is 18h, the extraction rate reaches the maximum, which is 87%, 65% and 53% respectively. At this time, as the concentration of the demulsifier increases to its critical micelle concentration (CMC), the demulsification effect is the best and the extraction rate reaches the maximum. When the amount of demulsifier added exceeds its CMC, the surface activity of the demulsifier reaches the maximum, the demulsification effect remains almost unchanged or even weakens with the increase of the demulsifier concentration, and the extraction rate tends to be constant or even decreases. Specifically in Figure 7 In b, when 50% DMSO is added, the extraction rate of PS plastic reaches the highest value of 76.8%. When the amount of demulsifier added is greater than 50%, its surface activity reaches the maximum value due to exceeding the CMC value of the demulsifier, the demulsification effect is weakened, and the extraction rate of PS microplastics decreases.

[0072] pass Figure 8It can be seen from a that compared with the ACN and EtOH demulsification treatments, after the DMSO demulsification treatment, the upper layer solution is enriched with more PMMA microplastics and has a better adsorption state with the oil droplets. This result is consistent with the above extraction results. Figure 8 b It can be seen that the enrichment pattern of PS microplastics is the same as that of PMMA.

[0073] (3) A 5 μm PMMA and 3 μm PS microplastic separation experiment was conducted with microplastic concentration and demulsifier addition amount as variables. The specific experimental conditions are as follows: in the olive oil emulsion, the water-oil ratio is 0.42, the volume of Tween 80 is 5%, and the volume of glycerol is 27%; in the demulsifier, its type is DMSO, and the demulsification time is 18 h; under the above experimental conditions, separation experiments were carried out at microplastic concentrations of 25 mg / L, 50 mg / L, 100 mg / L, and 200 mg / L, respectively, and separation experiments were carried out at each microplastic concentration with 40%, 50%, 60%, and 70% demulsifier addition amounts. The characterization results of the extraction rate at different demulsifier addition amounts and microplastic concentrations are shown in Fig. 9 In the figure, the extraction rate bars from left to right at the same concentration correspond to 40%, 50%, 60%, and 70% of the demulsifier addition amount respectively.

[0074] pass Fig. 9 a and 9b show that when 50% DMSO is added to the olive oil emulsion containing microplastics of different concentrations for demulsification treatment, the extraction rate reaches the maximum value, which is consistent with the previous research results. When the dosage of DMSO is 50%, the extraction rates of PMMA and PS microplastics of different concentrations are above 81.5% and 76.8%, respectively. Among them, the extraction rates of 200 mg / L PMMA and PS microplastics are 82.5% and 77.6%, which is different from the research results of Asma Batool et al. The surface functionalized fibers they invented have a significantly reduced removal rate for microplastics with a concentration greater than 50 μg / L due to the saturation of the surface adsorption sites. It can be seen that this experimental method has certain advantages for the efficient extraction of microplastics of different concentrations.

[0075] (4) A PS microplastic separation experiment was conducted with microplastic size as a variable. The specific experimental conditions were as follows: in the olive oil emulsion, the water-oil ratio was 0.42, the volume of Tween 80 was 5%, and the volume of glycerol was 27%; in the demulsifier, the type was DMSO, and the demulsification time was 18 h; under the above experimental conditions, microplastic separation experiments were carried out at microplastic sizes of 0.1 μm, 0.8 μm, and 3 μm, respectively, and separation experiments were carried out at various microplastic concentrations of 5 mg / L, 25 mg / L, 50 mg / L, 100 mg / L, and 200 mg / L at each size. The characterization results of microplastic extraction rates at different microplastic sizes and concentrations are shown in Fig.10 .

[0076] pass Fig.10 It can be seen that the extraction rate of the separation method of the present application for microplastics of different sizes and concentrations is above 73.6%. Among them, the extraction rate of 0.1μm and 0.8μm microplastics at 100mg / L is as high as 83.5%, which is close to the extraction rate of 83.7% of 3μm microplastics at 25mg / L, that is, this method has a high extraction rate for microplastics of different sizes. The above results show that this separation method has a certain applicability for enriching microplastics of different sizes.

[0077] (5) Comparative experiment: PS microplastic separation experiments were conducted on different oil phase emulsions. Since particle size is the main factor affecting emulsion stability, it is necessary to first construct relatively stable oil phase emulsions before conducting subsequent separation experiments for comparison.

[0078] Step 1: Preparation of CHCI3, C6H 14 , CH3(CH2)3OH, C4H8O2 emulsions, wherein the water-oil ratio is 0.42, the volume of Tween 80 is 5%, and the volume of glycerol is 27%. The particle size results of various emulsions prepared under the above experimental conditions are shown in Fig.11 a. By Fig.11 It can be seen that C6H 14 The particle size values ​​of CH3(CH2)3OH and C4H8O2 emulsions are 120.1nm and 131.1nm, which are close to the particle size value of the prepared olive oil emulsion of 132.3nm. In contrast, the particle size values ​​of CH3(CH2)3OH and C4H8O2 emulsions are larger, 431.4nm and 572.7nm. This is because the volume solubility of CH3(CH2)3OH and C4H8O2 in water is close to 8%, which is greater than that of C6H 14 (0%) and CHCl3 (0.8%) are more likely to undergo Ostwald ripening in the emulsion, resulting in droplet aggregation and increased particle size. Therefore, it is necessary to construct CH3(CH2)3OH and C4H8O2 emulsions with small droplet size and stability for subsequent experiments. Specifically, CH3(CH2)3OH and C4H8O2 emulsions with different amounts of Tween 80 were prepared, and the results are shown in the characterization. Fig.11 b. By Fig.11 b It can be seen that when the addition amount of Tween 80 is 7%, the particle size values ​​of CH3(CH2)3OH and C4H8O2 emulsions are 386.7nm and 205.3nm, respectively. At this time, the droplet size is small and has good stability. In summary, the conditions of oil-water ratio of 0.42, Tween 80 addition of 5%, and glycerol addition of 27% were selected to prepare C6H 14 and CHCl3 emulsions. CH3(CH2)3OH and C4H8O2 emulsions were prepared under the same oil-water ratio and glycerol addition amount, and the Tween 80 addition amount was 7%. In this way, emulsions with small droplet size and high stability can be prepared for subsequent comparative experiments.

[0079] Step 2: Based on the above experiments, PS microplastic separation experiments were carried out in different oil phase emulsions. The specific experimental conditions are as follows: the concentration of microplastics in the sample solution is 100 mg / L, and the size is 3 μm; in the olive oil emulsion, the water-oil ratio is 0.42, the volume of Tween 80 is 5%, and the volume of glycerol is 27%; the type of demulsifier is DMSO, and the demulsification time is 18 h; under the above experimental conditions, CHCl3, C6H 14 , CH3(CH2)3OH, C4H8O2 emulsion microplastic separation experiment, the fluorescence image of the obtained separation solution is shown in Fig.11 c, extraction rate results are shown in Fig.11 d.

[0080] pass Fig.11 It can be seen that C6H 14 The extraction rates of the three emulsions, CH3(CH2)3OH and C4H8O2, were all relatively low, below 30%. For CHCl3 emulsion, it had a relatively high extraction rate at 50% demulsifier addition, but it was still less than 60%. Under the same experimental conditions, the extraction rate of olive oil emulsion could reach 76.8% ( Figure 7 b), indicating that olive oil emulsion has obvious advantages in microplastic separation experiments.

[0081] 2. Using tea water as the sample and the amount of emulsion added as the variable, a microplastic separation experiment was conducted.

[0082] A large number of studies have shown that microplastics seriously pollute food and the environment. Among them, tea, as a popular beverage in China, is contaminated by the production and transportation environment and the microplastics released from tea bags. Therefore, a tea sample solution was prepared to conduct a microplastic separation experiment based on olive oil emulsion.

[0083] First, simulate the preparation of tea sample solution: add 2g of tea purchased from the market into 100mL of deionized water and heat at 90℃ for 60min. Then let the solution stand at 20℃ for 3 days, take 50mL of supernatant, add 3μm PS and 5μm PMMA fluorescent microplastics respectively, and prepare tea water with a microplastic concentration of 200mg / L. The two tea waters containing microplastics are stored at 20℃ for subsequent use. The following experiments set up tea water without microplastics added under the same conditions as a blank control.

[0084] According to the microplastic separation steps, microplastic separation experiments were carried out under the conditions of 10%, 30%, 50%, 70%, and 90% emulsion addition. The other experimental conditions are as follows: the water-oil ratio of the olive oil emulsion is 0.42, the volume of Tween 80 is 5%, and the volume of glycerol is 27%; the type of demulsifier is DMSO, the addition amount is 50%, and the demulsification time is 18h. The microplastic extraction rate was calculated according to the microplastic calculation steps. The characterization results of the extraction rate corresponding to different emulsion addition amounts are shown in Fig.12 a.

[0085] pass Fig.12 It can be seen that with the increase in the amount of olive oil emulsion added, the extraction rate of microplastics in tea leaves gradually increases. When the amount of olive oil emulsion added is 70%, the extraction rates of PS and PMMA microplastics are 79% and 80%, respectively. At this time, the separation effect of microplastics is the best, and the extraction rates of olive oil emulsion for PS and PMMA microplastics are close, indicating that olive oil emulsion has a certain applicability for extracting different types of microplastics in tea leaves.

[0086] 3. Using seawater as the sample and the amount of emulsion added as the variable, a microplastic separation experiment was conducted.

[0087] Millions of tons of plastic waste are discharged into aquatic ecosystems every year, which leads to serious plastic pollution in seawater. Studies have shown that many seas around the world are already polluted by microplastics. If the olive oil emulsion-based microplastic separation method can efficiently enrich microplastics in seawater, it is expected to be applied to the sampling and detection of seawater pollution.

[0088] First, simulated seawater sample solution was prepared: 500 ml of seawater was collected at the Qingdao beach, and after standing for 2 hours at 20°C, 200 mL of supernatant was taken and 3 μm PS and 5 μm PMMA fluorescent microplastics were added respectively to prepare seawater with a microplastic concentration of 30 mg / L. The two seawaters containing microplastics were stored at 20°C for subsequent use. The following experiments set up seawater without microplastics added under the same conditions as a blank control.

[0089] According to the microplastic separation steps, microplastic separation experiments were carried out with 10%, 30%, 50%, 70%, and 90% emulsion additions. Other experimental conditions are as follows: the water-oil ratio of the olive oil emulsion is 0.42, the volume of Tween 80 is 5%, and the volume of glycerol is 27%; the type of demulsifier is DMSO, the addition amount is 50%, and the demulsification time is 18h. The microplastic extraction rate was calculated according to the microplastic calculation steps. The characterization results of the extraction rate corresponding to different emulsion addition amounts are shown in Fig.12 b.

[0090] pass Fig.12b It can be seen that with the increase in the amount of olive oil emulsion added, the extraction rate of microplastics in seawater gradually increases. When the amount of olive oil emulsion added is 70%, the extraction rates of PS and PMMA microplastics are 71% and 75%, respectively, which is the best for the separation of microplastics. Mengmeng Sun et al. studied the removal efficiency of microplastics in seawater by building a magnetic miniature submarine, which is 70%, slightly lower than the microplastic separation effect of this application.

[0091] 4. Using soil water as the sample and the amount of emulsion added as the variable, a microplastic separation experiment was conducted.

[0092] Many studies have shown that the discharge of sewage and waste can lead to serious microplastic pollution problems in the soil. The soil is rich in difficult-to-degrade compounds and organic minerals, which will interfere with the analysis of microplastic problems. Therefore, soil sample solutions were prepared to carry out microplastic separation experiments based on olive oil emulsion.

[0093] First, simulate the preparation of soil sample solution: randomly weigh 5g of local soil and digest the organic matter in the soil using the Fenton method. Add 50mL H2O2 (10%), 5mL FeSO4·7H2O (2mmol / L), and 25mL H2O to the soil, adjust the pH to 3, stir thoroughly and let stand for 1h. Then, heat the solution at 90℃ for 2h until the liquid is completely evaporated. Finally, add 20mL of deionized water to the soil, mix thoroughly, take 15mL of the supernatant, add 3μm PS and 5μm PMMA fluorescent microplastics respectively, and prepare soil water with a microplastic concentration of 20mg / L. The two soil waters containing microplastics are stored at 20℃ for subsequent use. The following experiments set up soil water without microplastics added under the same conditions as a blank control.

[0094] According to the microplastic separation steps, microplastic separation experiments were carried out with 10%, 30%, 50%, 70%, and 90% emulsion additions. Other experimental conditions are as follows: the water-oil ratio of the olive oil emulsion is 0.42, the volume of Tween 80 is 5%, and the volume of glycerol is 27%; the type of demulsifier is DMSO, the addition amount is 50%, and the demulsification time is 18h. The microplastic extraction rate was calculated according to the microplastic calculation steps. The characterization results of the extraction rate corresponding to different emulsion addition amounts are shown in Fig.12 c.

[0095] pass Fig.12 c It can be seen that as the amount of olive oil emulsion added increases, the extraction rate of microplastics in the soil gradually increases. When the amount of olive oil emulsion added is 70%, the extraction rates of PS and PMMA microplastics are 72% and 83%, respectively, which is the best time for microplastic enrichment. And by comparing with other sample experiments, it can be seen that soil rich in impurities such as minerals has little effect on the separation of microplastics by olive oil emulsion.

[0096] 5. Using toothpaste as the sample and the amount of emulsion added as the variable, a microplastic separation experiment was conducted.

[0097] Many care products and cosmetics such as toothpaste, body scrubs and soaps contain microplastics to enhance their cleaning and exfoliating functions. However, there is a lack of research on the extraction of microplastics from toothpaste using the olive oil emulsion method; in addition, toothpaste is more complex than other actual samples and has better representativeness. Therefore, toothpaste sample solutions were prepared for microplastic separation and identification experiments.

[0098] Preparation of simulated toothpaste sample solution: Weigh 2g of toothpaste and dissolve it in 100mL of deionized water. Heat the solution at 50℃ for 10min to ensure that the toothpaste is dissolved. Then let the solution stand at 20℃ for 30min. Take the supernatant and add 3μm PS and 5μm PMMA fluorescent microplastics respectively to prepare tea water with a microplastic concentration of 10mg / L. The two toothpaste waters containing microplastics are stored at 20℃ for later use. The following experiments set up toothpaste water without microplastics under the same conditions as a blank control.

[0099] According to the microplastic separation steps, microplastic separation experiments were carried out with 10%, 30%, 50%, 70%, and 90% emulsion additions. Other experimental conditions are as follows: the water-oil ratio of the olive oil emulsion is 0.42, the volume of Tween 80 is 5%, and the volume of glycerol is 27%; the type of demulsifier is DMSO, the addition amount is 50%, and the demulsification time is 18h. The microplastic extraction rate was calculated according to the microplastic calculation steps. The characterization results of the extraction rate corresponding to different emulsion addition amounts are shown in Fig.12 d.

[0100] pass Fig.12 It can be seen from the figure that as the amount of olive oil emulsion added increases, the extraction rate of microplastics in toothpaste gradually increases. When the amount of olive oil emulsion added is 70%, the extraction rates of PS and PMMA microplastics are 74% and 82% respectively, which is the best time for the enrichment of microplastics. The above results show that olive oil emulsion is suitable for the enrichment of microplastics in toothpaste samples rich in minerals.

[0101] In the above experimental process, the preparation of sample solutions such as tea water and sea water all uses existing technologies.

[0102] (III) Microplastics identification experiment

[0103] 1. Raman spectroscopy characterization of the separation solution obtained with deionized water as the sample

[0104] Deionized water is a simple matrix and is basically not affected by the matrix itself during identification. Therefore, the separation solution obtained with deionized water as the matrix, i.e. the experimental sample, is matched with the peak position of the microplastic standard to determine the type of microplastics and further verify where the microplastics are enriched.

[0105] Standard product identification and analysis: 1 mL of 3 μm PS and 5 μm PMMA microplastic standards were placed on glass slides for Raman spectroscopy characterization. The characterization results are shown in Fig.13 a. The parameters of the confocal Raman microscope used were set as follows: laser wavelength 785nm, resolution 0.96cm -1 , the collection wave number range is 500-3000cm -1 The spectrum of Fig.13 It can be seen that the Raman spectrum of fluorescent PS microplastics is mainly at 994cm -1 、1594cm -1 There are vibration peaks. Among them, 994cm -1 The peak at 1594 cm is caused by the ring breathing vibration of the benzene ring. -1 The peak is caused by the stretching vibration of the benzene ring. The Raman spectrum of fluorescent PMMA microplastics is mainly at 809cm -1 There are vibration peaks, which are caused by the symmetrical stretching of COC. According to the microscope images of PS and PMMA in the corresponding spectra, PS and PMMA are dispersed spherical particles.

[0106] Identification and analysis of experimental products: The upper layer solution of the emulsion containing microplastics after demulsification also contains substances such as olive oil. These substances will interfere with the Raman signal. Therefore, the upper layer solution of the emulsion without microplastics after demulsification was used as a blank control, and the upper layer solution of the emulsion containing microplastics after demulsification was used as an experimental group for Raman spectroscopy characterization. The characterization results are shown in Fig.13 b. The separation experimental data corresponding to the identification experimental group are as follows: the microplastic concentration of the sample solution is 100 mg / L; the water-oil ratio of the olive oil emulsion is 0.42, the volume of Tween 80 is 5%, and the volume of glycerol is 27%; the type of demulsifier is DMSO, the addition amount is 50%, and the demulsification time is 18h.

[0107] Fig.13 In b, from top to bottom are the spectra of the blank control group (group I), the spectrum of the experimental group containing PS microplastics (group II), and the spectrum of the experimental group containing PMMA microplastics (group III). Among them, group II showed the 994, 1057, and 1594 cm -1 Characteristic peaks: Group III shows PMMA at 809 and 1434 cm -1Characteristic peaks, the characteristic peak results that appear are the same as the corresponding standard characteristic peak results or are consistent with the Raman identification peaks of micro- and nano-plastics in seawater studied by Raymond Gillibert et al., and the above characteristic peaks do not appear in the blank control group. This shows that the upper layer solution enriched with microplastics has characteristic peaks corresponding to microplastics. There is a microscope image of the upper layer solution corresponding to the spectrum on the spectrum side. It can be seen from the microscope image that PS and PMMA particles are regularly surrounded by the upper layer material, which indicates that the microplastic particles have been successfully extracted into the upper layer material. In summary, the upper layer material enriched with microplastics measured by Raman spectrometer has corresponding plastic characteristic peaks, which shows that Raman spectrometer can be used for the identification and analysis of separated microplastics.

[0108] 2. Raman spectroscopy characterization of the separated solution obtained using toothpaste as sample

[0109] Toothpaste is a complex matrix, and its components will interfere with the results during identification. Therefore, the spectrum of the separated solution obtained from the complex matrix after identification will be comprehensively compared with the spectrum of the existing reported results and the standard spectrum results to verify that the microplastics have been enriched and identified.

[0110] Identification and analysis of experimental products: The upper layer solution of the emulsion containing microplastics after demulsification also contains substances such as olive oil. These substances will interfere with the Raman signal. Therefore, the upper layer solution of the emulsion without microplastics after demulsification was used as a blank control, and the upper layer solution of the emulsion containing microplastics after demulsification was used as an experimental group for Raman spectroscopy characterization. The characterization results are shown in Fig.14 Specifically, the separation experimental data corresponding to the identification experimental group are as follows: the microplastic concentration of the sample solution is 100 mg / L; the water-oil ratio of the olive oil emulsion is 0.42, the volume of Tween 80 is 5%, the volume of glycerol is 27%, and the amount of emulsion added is 70%; the type of demulsifier is DMSO, the amount added is 50%, and the demulsification time is 18h.

[0111] Fig.14 In the figure, from top to bottom are the spectra of the blank control group (group I), the spectrum of the experimental group containing PS microplastics (group II), and the spectrum of the experimental group containing PMMA microplastics (group III). Among them, the 1058cm -1 Characteristic peak, which is Fig.13 The peak positions in b are consistent, and group III shows PMMA at 807, 1240, and 1734 cm -1Characteristic peaks, which are consistent with the peak position results reported by Tomoko Takahashi et al., and none of the above characteristic peaks appeared in the blank control. The above results show that after excluding the signal interference of the blank group, although there are some deviations in the data in the actual measurement, based on the extraction rate and the judgment results of other microplastic identification methods, it can be confirmed that the upper layer of microplastics enriched with microplastics has the corresponding characteristic peaks of microplastics, thereby determining the presence of PMMA microplastics. At the same time, from the microscope image corresponding to the spectrum, it can be seen that PS and PMMA particles are regularly surrounded by the upper layer of material, indicating that the microplastic particles in the toothpaste water are successfully extracted into the upper layer of material. In summary, the substances enriched in toothpaste determined by Raman spectrometer have corresponding plastic characteristic peaks, indicating that in actual samples, Raman spectrometer has certain potential to be applied to the identification and analysis of microplastics enriched in emulsions.

[0112] The above specific implementations cannot be used as limitations on the scope of protection of the present invention. For those skilled in the art, any replacement, improvement or change made to the implementations of the present invention falls within the scope of protection of the present invention. The parts not described in detail in the present invention are all known technologies to those skilled in the art.

Claims

1. A method for separating microplastics in a matrix based on an olive oil emulsion, characterized in that: The steps include: S1: prepare the sample solution of microplastics to be separated; S2: preparing an olive oil emulsion using olive oil, an emulsifier and water as raw materials in a high-speed disperser, wherein the emulsifier comprises Tween 80 and glycerol, Tween 80 accounts for 3%-9% of the total volume of the raw material, glycerol accounts for 9%-36% of the total volume of the raw material, and the volume ratio of olive oil to water is 0.24-1; S3: Thoroughly mix the sample solution with a certain volume of olive oil emulsion, wherein the olive oil emulsion is added to at least 60% of the total volume of the mixed solution; S4: Add a certain volume of demulsifier to the mixed solution. The demulsifier is DMSO, and its volume accounts for 40%-70% of the volume of the olive oil emulsion. After demulsification treatment for at least 13 hours, stand and separate the layers. The oil phase is an extraction solution enriched with a large amount of microplastics. Among them, in step S1, the type of microplastics separated is one of PS and PMMA.

2. The method for separating microplastics in a matrix based on an olive oil emulsion according to claim 1, characterized in that: The time in step S4 is at least 16 h.

3. The method for separating microplastics in a matrix based on an olive oil emulsion according to claim 1, characterized in that: The amount of demulsifier added in step S4 accounts for 50-70% of the volume of the olive oil emulsion.

4. The method for separating microplastics in a matrix based on an olive oil emulsion according to claim 1, characterized in that: The olive oil emulsion in step S3 was added to 70% of the total volume of the mixed solution.

5. The method for separating microplastics in a matrix based on an olive oil emulsion according to claim 1, characterized in that: In step S2, Tween 80 accounts for 5% of the total volume of the raw material, glycerol accounts for 27% of the total volume of the raw material, and the volume ratio of olive oil to water is 0.24-0.

62.

6. The method for separating microplastics in a matrix based on an olive oil emulsion according to claim 1, characterized in that: The sample solution in step S1 includes a sample solution of a simple matrix and a sample solution of a complex matrix, wherein the sample solution of the complex matrix is ​​one of toothpaste water, soil water, sea water, and tea water; the sample solution of the simple matrix is ​​a sample solution of deionized water.

7. The method for separating microplastics in a matrix based on an olive oil emulsion according to claim 6, characterized in that: The preparation method of toothpaste water is as follows: add toothpaste to water and stir thoroughly, let it stand and take the upper solution; the preparation method of soil water is as follows: first treat the soil with Fenton digestion solution, then mix the treated soil with deionized water, and take the upper solution; the preparation method of seawater is as follows: take seawater, let it stand for a period of time and take the upper solution; the preparation method of tea water is as follows: brew tea leaves with boiling water, then let it stand for a period of time and take the upper solution.

8. A method for identifying microplastics in a matrix based on olive oil emulsion, characterized in that: The method comprises the following steps: firstly preparing an extraction solution by the method for separating microplastics in a matrix based on an olive oil emulsion as described in any one of claims 1 to 7, and using an upper layer solution after demulsification treatment of an emulsion without microplastics as a blank control; collecting Raman spectra of the two, and determining the type of microplastics according to characteristic peaks of the Raman spectra.

Citation Information

Patent Citations

  • Method for mineralizing, enriching and separating environmental micro-nano plastic pollutants

    CN113119350A

  • Micro-plastic detection method

    CN114964988A